2019
DOI: 10.4028/www.scientific.net/jera.41.131
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Dried Leaves from Algerian Date Palm (<i>Phoenix dactylifera</i> L.) to Biogas by Anaerobic Digestion

Abstract: This work aimed to study anaerobic digestion of a new substrate made from the waste of Algerian date palm (Phoenix dactyliferaL.) in order to evaluate its biogas production capacity. The lignocellulosic component biodegradability and the process stability were also tested. Two reactors were launched with the same concentration of 20g total solid (TS)/L. A physical pre-treatment (grinding) of dried leaves lowered the substrate size below 2 mm. The theoretical methane yield (499 - 538 mL CH4/g of Volatile Solids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…After the fifteenth day we notice the stability of pH between 7 and 7.5 (optimum value for anaerobic digestion). This stability is caused by the decrease of volatile fatty acids concentration and the depletion of organic matter in the media (Djaafri et al, 2019). Volatile fatty acids (VFA) and volatile organic acid and buffer capacity (TAC) ratio Figure 8 showed that with the three concentrations and control sample the VFA / TA ratio begins near 1 in the first two days and begins to increase until exceeding 2 which is explained by the presence of the significant amounts of accumulated VFA, their accumulation influences negatively on the course of the anaerobic digestion (Kaidi et al, 2020).…”
Section: Anaerobic Digestion Of Date Pastementioning
confidence: 99%
“…After the fifteenth day we notice the stability of pH between 7 and 7.5 (optimum value for anaerobic digestion). This stability is caused by the decrease of volatile fatty acids concentration and the depletion of organic matter in the media (Djaafri et al, 2019). Volatile fatty acids (VFA) and volatile organic acid and buffer capacity (TAC) ratio Figure 8 showed that with the three concentrations and control sample the VFA / TA ratio begins near 1 in the first two days and begins to increase until exceeding 2 which is explained by the presence of the significant amounts of accumulated VFA, their accumulation influences negatively on the course of the anaerobic digestion (Kaidi et al, 2020).…”
Section: Anaerobic Digestion Of Date Pastementioning
confidence: 99%
“…The Adrar region has a great biomass potential, made up mainly of date palms (Phoenix dactylifera L.), covering about 27,804 hectares, with a total of 3,978,800 palms [8]. Every year, at the beginning of the new agricultural season, the palms are subjected to a maintenance and cleaning process that produces huge quantities of lignocellulosic biomass, between 10 kg/palm and 65 kg/palm, depending on the species [9][10][11][12]. Unfortunately, this biomass is undervalued.…”
Section: Introductionmentioning
confidence: 99%